Implementation of Technical Problem Solving Group Guidance Services to Improve Students' Critical Thinking Skills - Khairani, Maulida (Universitas Negeri Medan, 2025)
This study aims to improve students' critical thinking skills through Group Guidance services using Problem Solving Techniques. This study uses the type of research (PTBK) Action Research in Guidance Counseling. In this study, two cycles are used, consisting of several stages, namely: planning, implementation, observation, reflection, and evaluation. Each cycle will be evaluated. The subjects of this study were 10 students from class VIII-1 of SMP Negeri 5 Percut Sei Tuan. Data collection was conducted using questionnaires, observations, and documentation. Data analysis was performed by analyzing the questionnaire scores used during the Group Counseling service process. The results of this study indicate that after implementing the intervention in Cycle 1, there was a 40% increase in students' critical thinking skills. Following the provision of group counseling services in Cycle II, there was a significant increase of 90%. Therefore, it can be concluded that group counseling using the Problem Solving Technique can enhance the critical thinking skills of eighth-grade students at SMP Negeri 5 Percut Sei Tuan. The recommendations the author can provide for prospective guidance counselors and current guidance counselors are to use the Problem Solving Technique in implementing group counseling services. For schools, it is recommended to support counseling programs at schools that are related to improving students' critical thinking skills.